2013
DOI: 10.1177/0333102413477738
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the folate-related genes MTHFR, MTRR, and MTR and migraine with aura

Abstract: Aims The C677T variant in the methylenetetrahydrofolate reductase (MTHFR; EC 1.5.1.20) enzyme, a key player in the folate metabolic pathway, has been associated with increased risk of migraine with aura. Other genes encoding molecular components of this pathway include Methionine synthase (MTR; EC 2.1.1.13), and Methionine synthase reductase (MTRR; EC 2.1.1.135) among others. We performed a haplotype analysis of migraine risk and MTHFR, MTR, and MTRR. Methods Study participants are from a random sub-sample p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The first SNP MTRR rs162036 (Lys350Arg) is a missense polymorphism [ 84 ], which was found to be associated with vitamin B12 levels ( P = 4.00 × 10 −2 ) in 262 women of North European descent (no effect size available) [ 13 ]. The same authors, also identified a significant association ( P < 0.05) between the SNPs rs162048, rs1532268 and rs3776455 with vitamin B12 levels.…”
Section: Involved In the Catalysis Of Enzymatic Reactions In The One mentioning
confidence: 99%
“…The first SNP MTRR rs162036 (Lys350Arg) is a missense polymorphism [ 84 ], which was found to be associated with vitamin B12 levels ( P = 4.00 × 10 −2 ) in 262 women of North European descent (no effect size available) [ 13 ]. The same authors, also identified a significant association ( P < 0.05) between the SNPs rs162048, rs1532268 and rs3776455 with vitamin B12 levels.…”
Section: Involved In the Catalysis Of Enzymatic Reactions In The One mentioning
confidence: 99%
“…It has been reported that the polymorphisms rs1801133 (C677T) on MTHFR and rs1801133 (C677T) on MTHFR lead to a decrease in enzyme activity, causing Hcy accumulation in the body [11]. Hcyinjured endothelial cells and vascular smooth muscle cells induce the activation of procoagulant factors to maintain the body in a hypercoagulable state and promote thrombosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to migraine, most emphasis to date has been on the role of MTHFR polymorphisms, in particular the C667T variant, which is both common (minor allele frequency is 32.5% in 1000 Genome dataset), and results in a substantial reduction in enzyme activity. However, polymorphisms in other folate pathway enzyme genes have also been investigated for association with migraine, including 5‐methyltetrahydrofolate‐homocysteine methyltransferase (MTR), methionine synthase reductase (MTRR), TYMS, nicotinamide N‐methyltransferase, serine hydroxymethyltransferase 1, and MTHFD1 . MTHFD1 is a crucial enzyme of the folate pathway with multiple functions.…”
Section: Discussionmentioning
confidence: 99%
“…Oterino et al also found that a tandem repeat polymorphism in the TMYS promoter also interacted with MTHFR T667 to greatly increase the likelihood of experiencing aura in migraineurs . MTRR and MTR have also been investigated with respect to migraine and a haplotype of MTRR was associated with a reduced risk for MA . Therefore, interactions between SNPs within a gene, and between different genes of the folate pathway, may influence migraine susceptibility.…”
Section: Discussionmentioning
confidence: 99%